Is Percieved Quality Mediate the relationship between Brand Image and Country of Origin toward Purchase Intension? - Kussudyarsana Kussudyarsana; Yessy Bangkit Forma; Nur Achmad (Universitas Muhammadiyah Sidoarjo, 2020)
This study analyzes the effect of country of origin and brand image on purchnase intension through perceived quality as an intervening variable. The research setting was on Skin cares and Beauty clinic Industry. This research used incidental sampling as a sampling technique. This study involved 300 respondents which acces the online questionnaires through google form. The data obtained were processed used descriptive analysis and SEM analysis with SmartPLS. The results indicate that the country of origin positively effect on perceived quality. Meanwhile, the country of origin variable did not affect on purchase intension. The brand image variable has a positively impact on the perceived quality variable. Brand image has a positive effect on intension to buy. The perceived quality positively effects on intension to buy. Ccountry of origin indirectly effect on intension to buy through perceived quality. Brand image has an indirect effect on intension to buy through perceived quality as an intervening variable